In-situ tempetatures in the top 20 m of firn near the summit of Blåskimen Island, Western Dronning Maud Land - Goel, Vikram; Matsuoka, Kenichi (Norwegian Polar Institute, 2017)
This dataset contains a depth profile of temperature in top 20 m of firn near the summit of Blåskimen Island, Western Dronning Maud Land. The measurements were made using a thermistor string installed into a borehole. The thermistor was left for ~25 hours in the borehole. The data are provided in MATLAB (.mat) file format named ‘IRD_borehole_temp_dat.mat’ with following arrays- • ‘depth’ array with depth data in meters • ‘time’ array with time data in minutes • ‘temp’ matrix with each column containing temperature measurements with depth at a given time in degree Celsius. See the following manuscript for further details: Goel, V., Brown, J., and Matsuoka, K.: Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica, The Cryosphere Discuss., https://doi.org/10.5194/tc-2017-61, in review, 2017.